LOOP-MEDIATED ISOTHERMAL AMPLIFICATION ASSAY FOR RAPID AND SENSITIVE DETECTION OF PESTE DES PETITS RUMINANTS VIRUS IN FIELD CONDITIONS - W. Ashraf1a; H. Kamal1a; A. Mobeen; U. Waheed; H. Unger; Q. M. Khan1 (Journal of Animal and Plant Sciences, 2017)
Eradication of Peste des petits ruminants (PRR) is currently the center of attention of the Food and Agriculture Organization (FAO). The key to success of efforts put in eradication of PPR are hidden in efficient and sensitive diagnosis of the PPR. For thedetection of PPR virus (PPRV), molecular methods such as reverse-transcription PCR (RT-PCR) and loop-mediated isothermal amplification (LAMP) are preferred over serological assaysbecause to their higher sensitivity and specificity. However, molecular techniques are time consuming and require sophisticated laboratories for viral RNA extraction, reverse transcription, amplification and analysis steps. In the present study, single tube, LAMP was successfully established by incubating virus cultures or clinical sampleswitha special LAMP buffer and an amplification reaction system at 63°C for sixty minutes under isothermal conditions. In the test, the ESE-Quant tube scanner was used as heating block and fluorescenceanalyzer that can easily be operated in the field conditions by using rechargeable batteries. The new PPRV-LAMP setup excludes the need for pre-requisite steps of total RNA extraction and reverse transcription prior to the amplification of target viral genome and post amplification lengthy analysis by gel electrophoresis, thereby, providing with the option of field based sensitive, reliable and efficient molecular diagnosis of PPRV.Thesensitivity and reliability of the LAMP was compared with conventional RT-PCR. The amplified LAMP products were confirmed by both naked eye visualization and agarose gel electrophoresis.This power independent simplistic technology would result in the ease of PPRV diagnosis especially in the far from areas of disease endemic countries like Pakistan. In conclusion, this study provides an important field based molecular diagnostic tool for the detection and surveillance of PPRV.
Keywords: Peste des petitsruminants virus; PPRV; Loop mediated isothermal amplification; LAMP; Latest diagnostic methods for PPR